The Identity Challenges for The Education as a Social Institution - Matías González, Alberto (2018)
The fulfillment and social construction of the human identity is a permanent call to think over the theoretical basis that holds it, and the main goal of it. The present essay belongs to this kind of efforts. The objective of this research is just to achieve a theoretical approach to the meaning and influence of the identity construction of the value, for the nowadays education, under the struggling for the same social rights. This contribution lies on a grounded vision about education place while spreading the relation identity/difference, taking into account that the search for the same social rights is paramount to it. The reflexives notions are elaborated from the realities of all developing countries, in a century where the word suffers from a revolution in the field of technologies and where on the other hand flowers intolerance social fundamentalism. The main conclusion it is arrive at is that the search of equality in the difference, should be apriority for the social construction of identity, in it play an important role education.